2021
DOI: 10.1039/d1en00210d
|View full text |Cite
|
Sign up to set email alerts
|

Controllable synthesis of the defect-enriched MoO3−x nanosheets as an effective visible-light photocatalyst for the degradation of organic dyes

Abstract: Transition metal oxides (TMOs) are emerging as a promising class of photocatalysts for pollutants treatment. In this report, integrating the anti-solvent crystallization and thermal treatment, we develope a facile and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…[ 40 ] As a result, the length and width of the nanobelt appear along the c ‐axis and a ‐axis crystal orientation, respectively. However, the anion vacancy defects are generated in the c ‐axis direction by Ce doping, [ 37,41,42 ] which inhibits the crystal growth along the c ‐axis direction. The inhibition of crystalline growth along the c ‐axis direction is also proved by below X‐ray diffraction (XRD) data (Figure 3e), for example, compared to OV‐MoO 3 , the intensities of the {0 l 0} such as (020), (040), (060) planes and (200) plane in all Ce‐doped samples decrease remarkably, while the intensity of the (002) plane increases significantly, indicating that the Ce doping favors the growth along the a ‐axis and b ‐axis direction and results in the generation of nanoflakes.…”
Section: Resultsmentioning
confidence: 99%
“…[ 40 ] As a result, the length and width of the nanobelt appear along the c ‐axis and a ‐axis crystal orientation, respectively. However, the anion vacancy defects are generated in the c ‐axis direction by Ce doping, [ 37,41,42 ] which inhibits the crystal growth along the c ‐axis direction. The inhibition of crystalline growth along the c ‐axis direction is also proved by below X‐ray diffraction (XRD) data (Figure 3e), for example, compared to OV‐MoO 3 , the intensities of the {0 l 0} such as (020), (040), (060) planes and (200) plane in all Ce‐doped samples decrease remarkably, while the intensity of the (002) plane increases significantly, indicating that the Ce doping favors the growth along the a ‐axis and b ‐axis direction and results in the generation of nanoflakes.…”
Section: Resultsmentioning
confidence: 99%
“…The above results suggest that the CTAB also can serve as a structure inducer to promote the formation of Mo 5+ . [15] Inductively coupled plasma optical emission spectroscopy (ICP-OES) results point out that the mass ratio of Mo to Cu atoms is nearly 37.2 to 1, indicating that the molar ratio of PMA to TPyP-Cu is 2:1 (Table S1, Supporting Information). Besides, the matrix-assisted laser desorption/ionization time-of-flight mass spectrometry presents an obvious signal at m/z 2168, which can be assigned to [(H 4 PMo V 4 Mo VI 8 O 40 ) 2 (C 40 H 28 N 8 Cu)] 2fragment (Figure S10, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…The above results suggest that the CTAB also can serve as a structure inducer to promote the formation of Mo 5+ . [ 15 ]…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that defect engineering can improve the photocatalytic performance of MoO 3 . 37 MoO 3 with oxygen vacancies exhibited localized surface plasmon resonance (LSPR) effects, and the LSPR effect can broaden the light absorption range of semiconductors, thus improving the light absorption capacity. [38][39][40][41] In addition, oxygen vacancies can act as an electron trap to impede the recombination of photogenerated carriers.…”
Section: Introductionmentioning
confidence: 99%